1999
DOI: 10.1016/s0925-4773(98)00232-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of core binding factor Osf2/Cbfa-1 and bone sialoprotein in tooth development

Abstract: The transcription factor Osf2/Cbfa1 is a key regulator of osteogenic differentiation while BSP, a major non-collagenous protein, is a marker of osteoblastic differentiation. To determine the relationship between Osf2/Cbfa1 and the formation of mineralized tissues in tooth development we have studied the temporal expression of Osf2/Cbfa1 and BSP mRNA using in situ hybridization. These studies show that Osf2/Cbfa1 is expressed early in mesenchymal and epithelial tissues destined to form the mineralized tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
5
36
1
2
Order By: Relevance
“…1E). Our results were somewhat inconsistent with those of recent studies demonstrating Runx2/Osf2 gene expression in odontoblasts during tooth development, but after completion of tooth development, the principal site of expression of this gene was restricted to the PDL (D'Souz et al, 1999;Jiang et al, 1999). The reason for the discrepancies between those two studies and the present study is not clear at present.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1E). Our results were somewhat inconsistent with those of recent studies demonstrating Runx2/Osf2 gene expression in odontoblasts during tooth development, but after completion of tooth development, the principal site of expression of this gene was restricted to the PDL (D'Souz et al, 1999;Jiang et al, 1999). The reason for the discrepancies between those two studies and the present study is not clear at present.…”
Section: Discussioncontrasting
confidence: 99%
“…The reason for the discrepancies between those two studies and the present study is not clear at present. Since the signal detected in our study was clear and consistent with the previous observations concerning the expression of this gene in osteoblasts and PDL cells (D'Souz et al, 1999;Jiang et al, 1999), and since the signal disappeared completely when a sense probe was used, it is unlikely that the signals were non-specific. Differences in the probes used and in the differentiation stage of the animals in these studies may account for the discrepancies.…”
Section: Discussionsupporting
confidence: 92%
“…Cbfa-1 is a genetic transcription factor expressed in osteoblasts, and it is related to the expression of osteocalcin and osteopontin, which are known to be involved in the differentiation of osteoblasts with bone formation 3,17) . Recently, the expression of cbfa-1 has been confirmed in the tooth germ, but the mechanism involved remains unclear 4,7,10,13,20) . In this study, positive reactions for cbfa-1 were observed only in mesenchymal cells in the periodontal ligament, but not in cells of the lining epithelium or in odontogenic epithelial islands.…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors may also contribute to the Erk/MAPK effects, especially the aforementioned Cbfa1 since the activation of Cbfa1 is dependent on Erk/MAPK (26,44,55). Cbfa1 can regulate the expression of bone sialoprotein, type I collagen, osteocalcin, and osteopontin in osteoblasts (62)(63)(64)(65). Therefore, the inhibition of Erk activity in Erk1DN cells will prevent the activation of Cbfa1 leading to the inhibition of bone matrix protein deposition.…”
Section: Expression Of Erk1dn Protein Inhibited Cell Adhesion Spreadmentioning
confidence: 99%